2021
DOI: 10.1002/adfm.202102459
|View full text |Cite
|
Sign up to set email alerts
|

3D Printed Bioelectronic Microwells

Abstract: The in‐house and on‐demand fabrication of electrochemical integrated biosensors is a great challenge, especially in the field of modern point‐of‐care diagnostics. 3D printing technology allows the production of specialized electronic devices adapted to the required conditions, and 3D printed thermoplastic electrodes have shown hopeful achievements mainly in enzymatic bioassays. This work describes a novel configuration of integrated all‐3D‐printed electrochemical microtitration wells (e‐wells) for direct quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…There are also diagnostic applications where PLA was combined with carbon and carbon black. [53][54][55][56][57][58] The surface treatment of these materials was done with NaOH treatment, oxygen plasma, DMF, acetone and chloroform, electroplating, and deposition of materials. Some of their applications are the detection of hydrogen peroxide, C-reactive protein (CRP), dopamine, Hantavirus Araucaria nucleoprotein, Cd 2+ and Pb 2+ ions in real urine and saliva samples, glucose, and anti-microbial resistance.…”
Section: Plamentioning
confidence: 99%
“…There are also diagnostic applications where PLA was combined with carbon and carbon black. [53][54][55][56][57][58] The surface treatment of these materials was done with NaOH treatment, oxygen plasma, DMF, acetone and chloroform, electroplating, and deposition of materials. Some of their applications are the detection of hydrogen peroxide, C-reactive protein (CRP), dopamine, Hantavirus Araucaria nucleoprotein, Cd 2+ and Pb 2+ ions in real urine and saliva samples, glucose, and anti-microbial resistance.…”
Section: Plamentioning
confidence: 99%
“…antibody, bacteria or small molecule detection) on simple paper-based or 3D-printed microfluidic devices. [136][137][138] Measuring electrochemical signals is often achieved using bulky and expensive potentiostats, though there are now commercial options for portable handheld devices (such as PalmSens Sensit). 139 Still, their costs (>500 USD) and reliance on proprietary software remain prohibitive for many applications, particularly in resource-limited settings.…”
Section: Signal Transduction and Data Acquisitionmentioning
confidence: 99%
“…antibody, bacteria or small molecule detection) on simple paper-based or 3D-printed microfluidic devices. 136–138…”
Section: Processesmentioning
confidence: 99%
“…104 To date, most applications of 3D printed electrodes are focused on energy storage and conversion 105,106 applications and it has been demonstrated that 3D printed electrodes with commercial filaments are not directly active upon printing but require chemical and/or physical activation methods to render their surface highly electroactive. 107 Nevertheless, pristine 3D printed electrodes are still conductive enough to fabricate immunosensors for C-reactive protein 108 or enzymatic biosensors for cholesterol and choline 109 using multi-material 3D printing to print electrodes and electrochemical cells in a single print to obtain a fully functional device. Hence, more research is needed in the post-activation and modification steps of the electrodes and ideally in the formulation of conductive filaments to provide highly electrochemically active as-printed devices.…”
Section: Real-time Electrochemical Sensing: An Enriching Complement T...mentioning
confidence: 99%